KAJIAN PENERAPAN ENCODE DATA DENGAN BASE64 PADA PEMROGRAMAN PHP - Dadang Iskandar Mulyana (STIKOM CKI, 2016)
With the development of technology today and in order to obtain information quickly, information mealalui web site is the right media to fulfill this information and to design a website can use multiple programming languages one of which is PHP (Hypertext Prepocessor), because this script should be distributed in forms source, so it has some flaws and security vulnerabilities. Some drawbacks, one of which is a script can be easily copied, modified, or used in part / whole in other software without notice. In addition unencrypted scripts that make software that was built very vulnerable, because scripts can reveal some weaknesses of the software. Therefore, this study aimed to secure scripts from PHP (Hypertext Prepocessor) which will be distributed in order to awake the permissions and integrity, research using base64 algorithm by changing the structure of its index of plaintext when ciphertext attempted to be solved by breaking the code. Data modeling using stages in accordance flowchart that nothing has been described, with the way this protection, application developers who use the PHP programming language can hide php scripts that are not easily copied, modified partly / entirely by people who are not eligible and can secure the weakness of php application program flow, and makes one of the ways to secure information that was easily seen and can.Keywords: Base64, Encode, PHP.